Analisis Dampak Penerapan Nilai-Nilai Islam Pada Perusahaan terhadap Loyalitas Nasabah: Studi Kasus Nasabah Bank Syariah Mandiri KC XXX - Mardiana Mardiana (Iqtishodia: Jurnal Ekonomi Syariah, 2018)
This research is intended to analyze the effect of Implementation of Islamic Values ??on Customer Loyalty: Case Study at Bank Syaraiah Mandiri KC XXX. This research uses a quantitative approach with descriptive research type with the purpose of descriptive research and the characteristics of a particular population or region. For data collection, the researcher uses questionnaire methods from customers and interviews of employees of Bank Syariah Mandiri, documentation and literature study also related to this research. The results of this research indicate that the application of Islamic values ??has a significant influence on customer loyalty, because the value of sig <0.1, that is 0.000 <0.1, then the influence of the application of Islamic values ??(X) to customer loyalty (Y) is significant. Therefore, the result is equal to 68,2% it means the influence of variable of Islamic values ??to customer loyalty equal to 68,2%, while the rest that is equal to 31,8% caused by other factors not examined in this research.